2003
DOI: 10.1002/hlca.200390331
|View full text |Cite
|
Sign up to set email alerts
|

Automated Synthesis of Oligosaccharides

Abstract: Dedicated to Professor Duilio Arigoni on the occasion of his 75th birthdayThe chemical synthesis of oligosaccharides with an automated solid-phase synthesizer is described. An octenediol linker served to attach the growing oligosaccharide chain to the solid support, and the desired structures were cleaved from the support via olefin metathesis to afford a pentenyl glycoside. The automated syntheses of several important carbohydrates, including a pentarhamnoside, a proteoglycan linkage-region tetrasaccharide, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 49 publications
0
21
0
1
Order By: Relevance
“…For instance, using the automated approach, heptasaccharides (5b) were obtained in 24 hours in 42% overall yield, whereas the manual synthesis was much more laborious (14 days) and less efficient (9% overall yield) [90]. Working on expanding this promising technology, Seeberger and co-workers approached the synthesis of oligosaccharides containing other important residues and linkages, including aminosugars [91][92][93][94], sialic acids [95], furanosides [96], 1,2-cis glycosides [97], glycopeptides [98], and branched oligosaccharide sequences [69]. Codee et al reported the synthesis of β-mannosides [99][100] using essentially the same automation platform.…”
Section: Peptide Synthesizer-based Automation Of Polymer-supported Symentioning
confidence: 99%
“…For instance, using the automated approach, heptasaccharides (5b) were obtained in 24 hours in 42% overall yield, whereas the manual synthesis was much more laborious (14 days) and less efficient (9% overall yield) [90]. Working on expanding this promising technology, Seeberger and co-workers approached the synthesis of oligosaccharides containing other important residues and linkages, including aminosugars [91][92][93][94], sialic acids [95], furanosides [96], 1,2-cis glycosides [97], glycopeptides [98], and branched oligosaccharide sequences [69]. Codee et al reported the synthesis of β-mannosides [99][100] using essentially the same automation platform.…”
Section: Peptide Synthesizer-based Automation Of Polymer-supported Symentioning
confidence: 99%
“…[124] Die allgemeine Anwendbarkeit der automatisierten SPOS wurde an der Synthese eines Nonasaccharids, des Le yLe x (KH-1)-Antigenderivats 124 gezeigt (Schema 24). [125] Die Glycosylphosphate [126] Mit der automatisierten Oligosaccharidsynthese wurden verschiedene wichtige Kohlenhydrate synthetisiert, darunter das Globo-H-Hexasaccharid 133 (Schema 25), [128] das Kernpentasaccharid N-verknüpfter Glycane, [129] b-Mannosid, [130] Oligomannoside, [131] Oligorhamnoside, [132] die PhytoalexinElicitorfamilie aus Glucan [124a] und die parasitischen Impfstoffkandidaten gegen Malaria und Leishmaniose (siehe Abschnitt 7).…”
Section: 5-oxazolidinon-geschützte Sialyldonoren Für Effiziente Synunclassified
“…This latter linker is readily prepared from Merrifield resin and 4-octene-1,8-diol in one step, and affords the n-4-pentenyl glycosides which can be engaged in further glycosylations promoted by electrophilic reagents such as NIS. This linker has been applied to the synthesis of different polysaccharides [67][68][69], including the automated synthesis of antigens Gb-3 and Globo-H [70]. This linker has also been used for amino sugars such as the amino glycoside antibiotics and heparin.…”
Section: Cross-metathesis On Solid Phasementioning
confidence: 99%